Legal Protection Of Contract Employees Agreement In The Implementation Of Certain Time In Kendal (National Land Agency) - Aldila Marselli; Sunardi Sunardi; Sri Endah Wahyuningsih (Jurnal Akta, 2018)
Reforms in the field of employment law is done with the purpose to improve and enhance the quality of labor and personnel welfare. Reformation in the field of employment law begins with the issuance of Act No. 21 of 2000 concerning Trade Union / Labor United. Then followed with the release of Act No. 13 of 2003 on Manpower. Problems in this reasearch: (1) To identify and analyze the Implementation of the Employment Agreement in the Specific Time (PKWT) At the National Land Agency of Kendal. (2) To identify and analyze the forms of legal protection for workers at National Land Agency of Kendal with the Specific Time of Work Agreement (PKWT). The results of this study are: (1) Implementation of the Employment Agreement in the Specific Time (PKWT) at the Land Office of Kendal by implementing probation on each worker who recruits including contract workers. Which it is not supposed to apply probation at a certain time and labor agreements remain to be done if the employment agreement becomes null and void. (2) The legal protection of workers / laborers at Specific Time Work Agreement (PKWT) inemployeein practice has not run optimally, given the frequent violations, because of the vagueness of the rules on the implementation of the Employment Agreement for specific time periods, in providing protection against labor law for employees in the Land Office of Kendal.Keywords: Legal Protection; Labor Contract; the National Land Agency.